HUMAN RESOURCE DEVELOPMENT BASED ON KAYUH BAIMBAI VALUES TO OPTIMIZE EDUCATION QUALITY AT SMPIT BANJARBARU CITY - Annisa Zahra; Husnul Madihah; Agustina Rahmi (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to: 1) Analyze in depth how the implementation of human resource development based on the value of paddle baimbai in SMPIT Robbani and SMPIT ANIC Banjarbaru. 2) Evaluate the programs that have been implemented in human resource development in the two schools. 3) Analyze the obstacles and challenges faced. This study uses a qualitative approach with a case study type in the form of information in the form of descriptions. Documentation data collection techniques, observations, interviews with 2 principals, 5 deputy principals, and 4 teachers. Data processing techniques: reduction, data presentation and conclusion drawing. The results of the study show that: 1) The implementation of human resource development based on the value of paddle baimbai at SMPIT Robbani is carried out based on teamwork and collaboration. Meanwhile, in SMPIT ANIC is based on morals and self-potential. 2) Programs implemented at SMPIT Robbani include APNI, IHT, Kombel, Morning Instruction, Training, Workshop, Supervision, Coaching, tahsin and teacher tahfizh. At SMPIT ANIC, there are training, mentorship, leadership development, character development and English learning. 3) The obstacles faced by SMPIT Robbani are the time of activities at the same time as other activities, lack of understanding, limited human resources, difficulties in implementation, and lack of motivation. The challenge faced is maintaining commitment. Meanwhile, the obstacles to SMPIT ANIC are limited time and availability of resources, underestimating training, resistance and motivation. The challenge faced is to change the mindset and ensure consistency of implementation in schools.